Floral resources used by bees in urban areas: the case of Geneva, Switzerland - Heiniger, Charlène; Rochefort, Sophie; Prunier, Patrice (Frontiers in Ecology and Evolution, 2023)
It is now largely recognized that pollinators are threatened in agricultural habitats. Cities are thus seen as potential refuges for pollinators, if suitable green spaces are available, because they present favorable abiotic conditions for many pollinator species. However, data on resources used by bees in urban habitats are scarce. Moreover, promoting indigenous meadows in urban green spaces could help pollinator's survival. In this study, Apis mellifera was taken as a model to investigate potential difference in plant diversity used in agricultural and urban habitat. Pollen loads were sampled in 15 hives in both habitat types, using pollen traps. Then, the attractiveness of a melliferous meadow on wild bees was tested. To that end, a new seed mix (BF) including 35 indigenous plants producing nectar and/or pollen harvested by bees was developed and its attractiveness was compared to a seed mix widely used in Geneva (PFG). For most of the season, quantity and diversity of the pollen sampled was not significantly different between agricultural and urban habitats. Nevertheless, honey bees used different species in both habitats, probably because different plant communities are present.Sixty-one wild bee species were observed foraging in the new BF seed mix compared to only 47 species in the PFG. Likewise, more plants species were used in the BF seed mix than in the PFG. These results show that urban zones can be interesting for pollinators because they display diverse and abundant plant communities. Additionally, it shows that urban parks are species rich habitats, and that pollinator communities respond immediately to additional resources when available.